The choice of adjuvant radiotherapy in pancreatic cancer patients after up-front radical surgery - Xia Xiao; Pei Huang; Xiao-Ting Xu (PLoS ONE, 2025)
Background The role of adjuvant radiotherapy in pancreatic cancer following radical surgery remains a subject of of controversy. This study aimed to more accurately screen pancreatic patients who benefit from adjuvant radiotherapy. Methods Clinicopathologic characteristics of patients with resectable pancreatic cancer were collected from the Surveillance, Epidemiology, and End Results (SEER) database (2004–2015). Univariate and multivariate analyses were applied to identify prognostic factors affecting patient survival. All the patients were divided into two groups, one receiving radiation and the other not. Selection bias were reduced by propensity-score matching (PSM). Kaplan-Meier analysis was used to estimate overall survival (OS) and cancer-specific survival (CSS) between the two groups. Results Within 7097 patients, 2276 received adjuvant radiotherapy (external beam radiation), and 4821 did not. Multivariate analysis revealed that race, age, median income, sex, year of diagnosis, American Joint Committee on Cancer (AJCC) T stage, N stage, scope region lymph surgery, chemotherapy, and radiotherapy were independent predictors for overall survival of all the patients (all p < 0.05). After PSM, a total of 4304 patients were included. There was no OS and CSS benefit of radiotherapy compared with no-radiotherapy (all p > 0.05). Among patients with N1 stage, the radiotherapy group exhibited a median overall survival (mOS) of 21 months (95% CI, 19.82 to 22.18), while the non-radiotherapy group showed a slightly lower mOS of 18 months (95% CI, 16.88 to 19.12). Similarly, in terms of median cancer-specific survival (mCSS), the radiotherapy group demonstrated a mCSS of 22 months (95% CI, 20.79 to 23.21), whereas the non-radiotherapy group had a slightly shorter mCSS of 19 months (95% CI, 17.81 to 20.19). Radiotherapy reduced the all-cause mortality rate and cancer-specific mortality rate among patients with the N1 stage and T4 stage (all p < 0.05). In contrast, the patients in the radiotherapy group with the N0 stage (mOS, 28 months versus 34 months; mCSS, 30 months versus 41months), or primary focus on the body and tail of the pancreas (mOS, 23 months versus 29 months; mCSS, 25 months versus 32 months), or T1 stage (mOS, 36 months versus 113 months; mCSS, 36 months versus 104 months) exhibited a higher all-cause mortality rate and cancer-specific mortality rate compared to those without radiotherapy (all p < 0.05). Subgroup analysis indicated N1 stage pancreatic cancer patients with T2-4 stage, primary focus on the head of the pancreas, young age of onset, and combination chemotherapy were in favor of the adjuvant radiotherapy group (all p < 0.05). Conclusions Our analysis demonstrates that adjuvant radiotherapy may be beneficial for N1 stage (N+) pancreatic cancer patients who have undergone up-front radical surgery with T2-4 stage, primary focus on the head of the pancreas, young age of onset, and receiving combination chemotherapy. However, radiotherapy needs to be used with caution in patients with T1 stage, N0 stage (N-), or primary focus on the body and tail of the pancreas. These findings may contribute to the development of personalized selection criteria for adjuvant radiotherapy in post-surgical pancreatic cancer patients.